2008
DOI: 10.1186/1476-072x-7-18
|View full text |Cite
|
Sign up to set email alerts
|

A GIS-based method for household recruitment in a prospective pesticide exposure study

Abstract: Background: Recent advances in GIS technology and remote sensing have provided new opportunities to collect ecologic data on agricultural pesticide exposure. Many pesticide studies have used historical or records-based data on crops and their associated pesticide applications to estimate exposure by measuring residential proximity to agricultural fields. Very few of these studies collected environmental and biological samples from study participants. One of the reasons for this is the cost of identifying parti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 34 publications
0
12
0
Order By: Relevance
“…We argue that no matter what initial geocoder is used, some level of manual intervention/interactive geocoding will always be required within any geocoded datasets because address data are routinely reported in vague terms and even the highest quality address data will be beholden to the accuracy of the geocoding process used. The frequent use of the manual methods for improving inaccurate geocodes in the available literature seems to support this [ 2 , 11 , 14 , 15 , 17 - 19 , 26 - 29 , 34 - 36 ].…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…We argue that no matter what initial geocoder is used, some level of manual intervention/interactive geocoding will always be required within any geocoded datasets because address data are routinely reported in vague terms and even the highest quality address data will be beholden to the accuracy of the geocoding process used. The frequent use of the manual methods for improving inaccurate geocodes in the available literature seems to support this [ 2 , 11 , 14 , 15 , 17 - 19 , 26 - 29 , 34 - 36 ].…”
Section: Discussionmentioning
confidence: 96%
“…The accuracy of the satellite imagery, road vectors, and geocoding used for the Google Maps API is dependent on the underlying Navteq and Tele Atlas data. However, manual geocoding with aerial/satellite imagery has been proposed as a substitute for ground truth data in the literature [ 34 , 42 ] and has been used as such on numerous occasions [ 2 , 6 , 11 , 15 , 18 , 19 , 25 , 28 , 29 , 35 , 36 ]. Our approach also assumes that the Google Maps API and associated data are available in the region(s) of interest.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In 1996 an algorithm was developed for use in a GIS to model the surface movement of insecticide in response to rainfall as modulated by slope, soil, management practices, and time of insecticide application. This algorithm estimated the loss of pesticides from field areas, run-off flow patterns, and the accumulation of pesticides at lower levels in response to rainfall [17]. GIS was also utilized to visualize and analyze four residual pesticides, endosulfan, diazinon, dichlorvos, and deltamethrim, in both land and water.…”
Section: Discussionmentioning
confidence: 99%
“…Remote sensing technologies such as geographic information systems, which better tracks pesticide and other environmental exposures, as opposed to relying on records-based data and residential proximity to associated pesticide applications, may provide more statistical power and plausibility of exposure paradigms to epidemiologic and associative studies [152]. Combining several of these approaches, as well as subsequent computational biology and functional studies of identified variants, should improve understanding and diagnostic techniques related to PD.…”
Section: Emerging Frontiers and Future Directionsmentioning
confidence: 99%